Aktivitas Antioksidan dan Karakteristik Kimia Stik Pegagan - Distya Riski Hapsari; Siti Nurhalimah; Arti Hastuti; Aprilia Pratami (JURNAL AGROINDUSTRI HALAL, 2024)
Gotu kola leaves contain active compounds which are beneficial for the human body. Gotu kola leaves can be added to processed foods, including sticks. This research added sticks with a concentration of 10%, 15%, and 20% of gotu kola leaves paste. Then, antioxidants activity, crude fiber content, water content, ash content, protein content, fat content, and carbohydrate content were analyzed. After that, gotu kola sticks were selected. Based on research results, the greater the addition of gotu kola leaves, the greater the antioxidant activity, water content, ash content, protein content, and crude fiber content. Gotu kola sticks were selected with the addition of 15% gotu kola leaves. The results of gotu kola chosen sticks had an antioxidant content of 53671.90 ppm, water content 1.32%, ash content 0.99%, protein content 7.75%, fat content 39.04%, carbohydrate content 50.91% and crude fiber 32.20%.